Impact of Institutional Credit on Income : A Study of Farmers in Haryana - Gaur, Arti; Kaushal, Neelam (AMC Indian Journal of Entrepreneurship, 2018)
Agriculture has been associated with production of essential food crops. At present, agriculture above and beyond farming includes forestry, dairy, fruit cultivation, poultry, bee keeping, mushroom, arbitrary, etc. Today, processing, marketing, and distribution of crops and livestock products are all acknowledged as part of agriculture. Thus, agriculture can be referred to as production, processing, promotion, and distribution of agricultural products. Agriculture plays a critical role in the life of an economy. Agriculture is the backbone of the economic system of a country. In addition to providing food and raw materials, agriculture also provides employment opportunities to a very large percentage of the population. This study assesses the impact of institutional credit on income of farmers. It is a study based on primary data. An attempt was made to analyze the impact of income of farmers.Â